2021
DOI: 10.1017/jfm.2020.857
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear mechanism of the self-sustaining process in the buffer and logarithmic layer of wall-bounded flows

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 82 publications
(139 reference statements)
1
21
0
Order By: Relevance
“…Additionally, the azimuthal or oblique vortex, which seems to be the precursor of a streamwise vortex, is located between a HSS and a LSS. This configuration supports and gives further physical insight into the flow structures (sheared spanwise vortices located between oblique alternating streaks), which, through nonlinear interactions, form the dominant forcing mode associated with streamwise vortex regeneration (Bae et al 2021). The physical mechanisms responsible for the observed vortex autogeneration are further examined in § 5.…”
Section: Velocity Structuresmentioning
confidence: 52%
See 4 more Smart Citations
“…Additionally, the azimuthal or oblique vortex, which seems to be the precursor of a streamwise vortex, is located between a HSS and a LSS. This configuration supports and gives further physical insight into the flow structures (sheared spanwise vortices located between oblique alternating streaks), which, through nonlinear interactions, form the dominant forcing mode associated with streamwise vortex regeneration (Bae et al 2021). The physical mechanisms responsible for the observed vortex autogeneration are further examined in § 5.…”
Section: Velocity Structuresmentioning
confidence: 52%
“…Similarly, recent particle image velocimetry results in TBL (Lee, Hutchis & Monty 2019) show that high-shear layers are formed due to the collision of large-scale structures travelling at different convection velocities. A very recent numerical study conducted on minimal channels at low and high Reynolds numbers by Bae et al (2021) revealed that when the most amplified nonlinear mode, identified through the use of resolvent analysis, is removed, the turbulence intensity in the buffer and logarithmic layers is significantly reduced. The same study determined by conditional averaging that the flow structures associated with the dominant nonlinear interactions of the SSP that regenerate streamwise vortices are sheared-spanwise vortical structures and oblique alternating streaks.…”
Section: Near-wall Organisation and Turbulence Self-sustaining Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations